Integration of spendings on the agricultural sector in the national budget and the budgets of voivodes in Poland in the long term (2000-2013) = Integracja wydatków na sektor rolny w budżecie centralnym i budżetach wojewodów w Polsce w długim okresie (2000-2013) - Czyżewski, Andrzej; Matuszczak, Anna (Zielona Góra: Faculty of Economics and Management Press)
The purpose of this article is to identify the areas of integration spendings on the agricultural sector in the national budget and the budgets of voivodes in the years 2000-2013, with an indication of the processes of their complementarity and substitutability. There was analyzed the expenditures of national and the EU budget flowing to the agricultural sector in Poland, showing their significant increase after the Polish integration with the EU. Was noticeable, however, that increasing spendings on the agricultural sector from the national budget could be "enforced" by increasing funding from the EU. This indicates the integrity understood as complementary to each other. Then shown the complementarity and substitutability spendings on the agricultural sector in the central agricultural budgets and the budgets of voivodes with regard to the financing of projects involving EU funds, noting ongoing trends.
Keywords: sektor rolny; budżet centralny; budżety wojewodów; wydatki; komplementarność; substytucyjność; agriculture; central budget; budgets of vovodes; expenses; complementarity; substitutability